Comparison of malnutrition assessment tools in terms of revealing the relationship between polypharmacy and inappropriate drug use and malnutrition - Cakmak, Guzin; Öztürk, Zeynel Abidin (Progress in Nutrition, 2021)
Malnutrition is prevalent among older adults and is associated with morbidity and mortality. This study aims to investigate the relationship between malnutrition and polypharmacy in older adults. We also tested which malnutrition test had a stronger relationship with polypharmacy. We conducted a cross-sectional study for four months. We assessed malnutrition by mini nutritional assessment short-form (MNA-SF), long-form (MNA-LF), and Global Leadership Initiative on Malnutrition criteria (GLIM). We evaluated potentially inappropriate medication (PIM) use was by TIME criteria (Turkish Inappropriate Medication Use in the Elderly) criteria. Data analysis was done by SPSS version 22. The study population was composed of 93 women and 57 men, of mean age 73 +/- 9 years. Polypharmacy was present in 73% (n=110) of them. MNA-SF, MNA-LF and GLIM scores were correlated with presence of polypharmacy (p=0.036, p=0.002, p=0.045). MNA-LF was associated with polypharmacy in linear regression analysis (r²=0.06, p=0.046). PIM use was also found to be negatively related to MNA-LF scores (p=0.049, r=-0.166). We demonstrated a cut-off value of 6.5 of drug numbers for being malnourished (sensitivity 80%; specificity 88%; CI:95%; AUC:0.844; p